Pandangan Martin Luther tentang Pembenaran oleh Iman dalam Yakobus 2:14-26 - Maria Payer; Antonius Missa; Bobby Kurnia Putrawan (Sekolah Tinggi Teologi Torsina Surakarta, 2022)
In this paper, the authors explain that the views of a reforming theologian named Martin Luther once stated that the letter of James